MEDICINAL EFFECT REVIEW OF AGARWOOD LEAVES FROM AQUILARIA AND GYRINOPS GENERA - Wangiyana, I Gde Adi Suryawan (Jurnal Silva Samalas, 2020)
Aquilaria and Gyrinops are the most common genera of Agarwood in Indonesia. These two group have wide distribution in Indonesia. Therefore, Indonesia is one of the biggest agarwood commodity producer in the world. However, the resin on agarwood stem is still main utilization of agarwood commodity in this country. Diversification agarwood utilization other than resin is needed to maximilize the potency of this commodity. Agarwood leaves are one of by product from agarwood cultivation that rarely been utilized. Agarwood leaves contain secondary metabolites that have medical effect such as Phenol, Flavonoid, Terpenoid , Alkaloid and Tannin. Thus, agarwood leaves has a good potency as a source of food and beverage product that have a medicinal effects. Agarwood leaves form Aquilaria group and Gyrinops group both have medicinal effect including antioxidant, antibacterial, cytotoxic and anticancer. Aquilaria leaves also has additional medicinal effect including: anti-inflammatory, anti-diabetic and laxative while Gyrinops leaves also has additional medicinal effect as antiradical source of sunscreen.